Réponses

Meilleure réponse !
2014-10-24T23:34:12+02:00
2x+7=0    2x=-7    x=-7/2     :    solution = -7/2

(x-5) carré=0  x-5=0  x=5              solution=5

12x+3=x+2      11x=-1    x=-1/11        SOLUTION=-1/11

xcarré=9    x=3  ou x=-3          solutions= 3 et -3

xcarré-4x+4=0    (x-2)carré=0    x-2=0  x=2      solution = 2
2014-10-25T00:20:09+02:00
Bonjour
1) 2x + 7 = 0⇔ x=-7/2
(x - 5)(au carré) = 0 ⇔x - 5 = 0⇔x=5
12x + 3 = x + 2⇔11x=-1⇔x=-1/11
x (au carré) = 9⇔x=3 ou x=-3
x (au carré) - 4x + 4 = 0⇔(x-2)au carré=0⇔x-2=0⇔x=2